Early Suspicion of Heparin-Induced Thrombocytopenia for Successful Free Flap Salvage: Reports of Two Cases - Mehdizade, Turan; Kelahmetoğlu, Osman; KELAHMETOĞLU, OSMAN; Gürkan, Volkan; GÜRKAN, VOLKAN; Çetin, Güven; ÇETİN, GÜVEN; Güneren, Ethem; GÜNEREN, ETHEM (My University, 2020)
Heparin-induced thrombocytopenia (HIT) is an underestimated complication of heparin treatment. Flap loss and related morbidity (even mortality) are caused by occlusion of the capillary vessels by a highly immunogenic complex formed by adherence of antiheparin antibodies to platelet factor 4. Early suspicion and effective treatment of HIT developing in two free flaps are described. We report on the management of two patients with HIT. Both patients were treated successfully by early suspicion and hematology consultation. Heparin products were discontinued; the patients were switched to a nonheparin anticoagulant. We emphasize the importance of early diagnosis, hematologist assessment, and a change to a nonheparin anticoagulant to prevent flap failure and possibly the catastrophic consequences of such failure.
Keywords: flap; fondaparinux; heparin-induced thrombocytopenia; surgery